Kinerja Bank Badan Usaha Milik Negara Sebelum dan Sesudah Peluncuran Danantara - Hastuti Widyaningsih (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to examine the differences in performance of state-owned banks incorporated into Danantara before and after the launch of Danantara. Bank performance is measured using ROA and ROE. This study uses a quantitative approach with the mean difference test method and is processed using Ms Excel. The data in this study consists of three banks incorporated into Danantara: Bank Mandiri, Bank BRI, and Bank BNI. The results show that the performance of state-owned banks after the launch of Danantara is better compared to the previous period. It can be concluded that the results of this study support the stakeholder theory.